The Study of Zamyatin's Weltanschauung - Ewart, Laura (My University, 1972)
The study of Zamyatin's Weltanschauung and its presentation in his works.
The thesis contains a preface, five chapters and a conclusion. Chapter I attempts to define Zamyatin's concept of man as presentated in his novel Mbd. Chapter II deals with the two forces energy and entropy. Chapter III discusses the effect of entropy on man and as presented in Zamyatin' s creative writings. Chapter IV presents Zamyatin's view of literature and its role. Chapter V portrays some of Zamyatin's literary techniques which he employed to procure reader participation. The Conclusion summarizes Zamyatin's world outlook and evaluates his philosophy.
Keywords: Russian; Other Languages, Societies, and Cultures; Other Languages, Societies, and Cultures